Inflammatory Nasal Swelling due to Leishmania tropica. (27th December 2021) - Fellah, Hajiba; Hakkour, Maryam; Delouane, Bouchra; Hmamouch, Asmae; Bouyahya, Abdelhakim; Sebti, Faiza; Sadak, Abderrahim
Abstract : Since its discovery in the 19th century, cutaneous leishmaniasis has been a major public health problem, especially with the appearance of more and more unusual cases of cutaneous lesions due to this parasite. Indeed, the present study joins the previous studies and describes a typical case of a nasal lesion due to Leishmania infection. This is a 20-year-old young man, with no particular pathological history, from an epidemic focus who presented with inflammatory nasal swelling similar to a mucocutaneous form. However, the X-ray data showed that no lysis of the bones proper to the nose was detected and no damage to the underlying mucosa was observed. Nevertheless, the parasitological diagnosis confirmed the presence of amastigotes, and the results of the molecular study showed that the electrophoretic profile was comparable to that of L. tropica . After diagnosis and confirmation, treatment with meglumine antimonate at the rate of two ampoules/injection (one ampoule = 5 ml) of antimony salt for one month was administered intramuscularly with favorable outcome. Atypical forms of cutaneous leishmaniasis constitute a rare and unusual entity often leading to diagnostic delay. For this, the clinical examination must take into account both exceptional presentations of Leishmania infection, in particular in subjects living or having stayed in an endemic area, in order to ensure appropriate and early treatment.